Optimal control of a NASCAR – specification race car. Issue 5 (4th May 2023) - Limebeer, D. J. N.; Bastin, M.; Warren, E.; Fensham, H. G.
Abstract : This paper adapts the minimum-lap-time simulation technologies developed in Formula One to NASCAR. The adaptation process requires recognition of the variable lateral curvature of some tracks, as well as the asymmetries of NASCAR-specification race cars that have been configured for high-speed oval tracks that are dominated by left-hand cornering. These asymmetries include different suspension characteristics on the left- and right-hand ends of each axle, different left- and right-hand tyres on each axle, as well as asymmetries in the car's aerodynamic performance. The results compare optimal control calculations, industrial simulation-based predictions and race-captured telemetry data. For the most part, these various data sources are in good agreement, with the importance of variable lateral camber highlighted. It is demonstrated how race car drivers have to find the best compromise between the conflicting objectives of exploiting the additional camber available on the outside of variable-camber tracks and increasing the travelled distance and racing line cornering curvature.